IMPLEMENTATION OF THINK TALK WRITE (TTW) MODEL TO IMPROVE POETRY WRITING SKILL ON FOUR GRADE STUDENT - Febi Sulistyo Rini; Muhammad Ismail Sriyanto; Idam Ragil Widianto Atmojo (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Lowness of poetry writing skill on four grade student of jetis 2 primary school makes researcher done a research with Think Talk Write model of study. The purpose of this research was to improve poetry writing skill on student. The type of this research was Classroom Action Research because to emphasize improvements in classroom learning. Result of this research was average score of students’ poetry writing on first test before the action done was 47. After cycle one, the score increased to 71,83, and at cycle 2 it became 77,67. The previous classical comprehensiveness of poem writing skill was 20%, then increased to 60% on first cycle, and rose again into 77,67% on second cycle.The conclusion of this research was the implementation of Think Talk Write (TTW) model can improve students’ skill on writing poetry on four grade students of Jetis 2 Primary School in academic year of 2017/2018.